Community Participation Level of Penggung Village on the Agropolitan Region Development in Kecamatan Bandar Nawangan, Kabupaten Pacitan - Pratiwi, Jenvia Rista; Parmawati, Rita; Rifai, Ridwan Muhamad (Postgraduate School of Universitas Brawijaya, 2023)
Pacitan Regency owns abundant natural resources, one of which is in the agricultural sector. In accordance with the RTRW of Pacitan Regency 2005-2025, there is a development plan for the Agropolitan Area in Bandar and Nawangan Sub-districts. This research aims to find out how the level of community participation in the development of the Agropolitan Area of Bandar Nawangan Subdistrict, Pacitan Regency. The descriptive quantitative approach was used to understand how community involvement in Agropolitan Area development planning. The level of community participation was measured using Arnstein's concept (A Ladder of Citizen Participation) and showed the level of community participation at the informing level, which is included in the tokenism classification. This study’s results recommended assistance to local leaders to have similar goals as the government as the means of increasing community participation. The village leaders have greater influence or control because of their proximity to the community. As a consequence, community participation in the development of the Agropolitan Area of Bandar Nawangan Sub-district, Pacitan Regency will be escalated. Keywords: agropolitan, participation level, arnstein